Študijske delavnice s področja energijsko učinkovitih lesenih objektov - Žegarac Leskovar, Vesna (Les (Ljubljana), 2011)
The progressive orientation of the sciences of architecture and civil engineering towards energy-efficient planning and construction has been evident in Slovenia for a considerable period of time. Nevertheless, successful search for new solutions depends on integrating expert knowledge, industry, practical experience and innovative ideas. At the Faculty of Civil Engineering, University of Maribor, we strive for such integration through study workshops which proved to be highly interesting to students and their mentors on the one hand and to partners from the relevant branches of industry on the other, all of which helps our goal to build awareness about the mentioned issues among future architects and civil engineers. The first study workshop on energy-efficient timber buildings held in 2010 was focused on single-family prefabricated timber-frame houses with special attention being paid to the increased glazing size. The study workshop held in this year was focused to the public buildings and thus practically means a continuation and a progress in designing of prefabricated timber structures. Given its characteristics stated above, timber combined with properly oriented glazing surfaces certainly has a huge development potential also in constructing public buildings, i.e. in the field that has currently not reached enough interest or attention among Slovene manufacturers and investors.
Keywords: energijska učinkovitost; lesena gradnja; steklo; načrtovanje; modeliranje; delavnice